Fluidized Bed Design Parameters Affecting Novel Lactic Acid Downstream Processing - Sosa, Ana V. (2001)
Lactic acid purification was directly done from fermentation utilizing a fluidized bed column refilled with a strong anionic exchange resin. The purpose of this work was to study the influence of two important design parameters, bed‐diameter (D) and bed‐height (H), in the lactic acid binding and elution capacity of the matrix. By changing the settled bed height from 2.5 to 5 cm for each diameter of column analyzed it was possible to obtain an 50% increase in the binding capacity of the resin in all experiments. This fact was attributed to a higher contact time between the culture broth and the anionic resin produced by the increase of back mixing and lactic acid residence time.